Big Data as the subject of a transaction in civil turnover under the law of the Russian Federation (Revista de Investigaciones Universidad del Quindío, 2022)
The article aims to investigate the issues concerning the definition of the big data concept, as well as the problem of civil turnover of big data in the legislation of the Russian Federation. Approaches to this definition enshrined in doctrinal legal acts and investigated in the legal literature are analyzed. The features and peculiarities of big data are considered. The conclusion about the need to legislate the basic categories in the field of big data to clarify the place of this object in the system of objects of civil rights is made. The study has also analyzed the risks of including big data in civil law turnover. Given the results, substantially practical approaches to regulating civilized forms of big data circulation should be the established mechanisms of civil liability for the use of big data that have resulted in derogation or limitation of the rights of citizens.
Keywords: big data; objects of civil rights; digital assets; intellectual property; information